Recovering the Loss: Infanticide, Ambivalence and Trauma in Shobha Rao’s The Lost Ribbon - Mitali Mishra; Surbhi Saraswat (IAFOR Journal of Arts & Humanities)
This paper examines the narrative The Lost Ribbon from Shobha Rao’s 2006 collection An Unrestored Woman through the lens of Motherhood Studies. It argues that the act of infanticide, central to the story, must be understood as deeply rooted in the structural inequalities and patriarchal ideologies inherent in the Recovery Operation during the Partition of India. The analysis situates the phenomenon of infanticide within broader historical and cultural contexts in India, as well as within the disciplinary framework of psychiatry. Drawing on theoretical perspectives on maternal ambivalence, the paper expands on Adrienne Rich’s distinction between mothering as lived experience and motherhood as a patriarchal construct. It contends that, contrary to the abstract ideal of a “natural” mother, the subjectivity of the mother in the story is shaped by patriarchal forces that produce a profound and traumatic ambivalence about her identity and belonging. The legal imposition of repatriation to a nation that rejected her children underscores the tension between patriarchal state imperatives and maternal agency. Finally, the paper interrogates the rights of children born to inter-religious parents during a period when religion was the primary determinant of citizenship, highlighting critical questions that remain relevant for contemporary discourse.